Absence of surface flaking in hierarchical glass-ceramic coating: High impact resistant ceramic tiles. Issue 14 (November 2019) - Enríquez, E.; Fuertes, V.; Cabrera, M.J.; Seores, J.; Muñoz, D.; Fernández, J.F.
Graphical abstract: Abstract: The impact resistance method is a useful procedure to determine the tile resistance. While other works are focused on modifying the tile support to improve the impact resistance, in this work, a new glass-ceramic material was developed to used it as glaze coating in order to relax impact tensions. This material possesses a hierarchical nano-microstructure consisted of microcrystal surrounded by nanostructured regions having low glassy phase, which is considered responsible for tension relaxations. The resilience coefficient measured in conventional and glass-ceramic glazes presents little differences (0.85–0.88). However, impact damages on the surface is totally inhibited for glass-ceramic coating while the conventional one suffers great flaking. These damages were analyzed by Optical profilometry and FESEM to compare the impact resistance and to correlate it with its microstructure. The results confirm that the micro-nanostructured coating paves the way to improve impact resistance in ceramic materials where surface damage is a critical parameter.